Comprehensive single-cell sequencing reveals the tumor microenvironment and tumor-specific characteristics in trachea squamous cell carcinoma - Wang, Hongwu; Li, Hongli; Zou, Heng; Meng, Han; Liu, Yan; Ban, Chengjun; Yu, Weixia; Cheng, Miao; Teng, Jun (Frontiers in Oncology, 2025)
Trachea squamous cell carcinoma (TSCC) is a subtype of lung cancer. A thorough investigation of the tumor microenvironment of TSCC is crucial for the development of cancer therapeutics and predicting clinical responses. In this study, we utilized single-cell RNA sequencing to analyze seven TSCC samples (including five malignant and two non-malignant samples) and obtained 70,682 high-quality cells. Based on the expression levels of marker genes, we identified 7 major cell types within the samples. By comparing malignant samples that received chemotherapy with those that did not, we identified critical transcriptional regulators responsible for T cell state transition in response to chemotherapy. Additionally, we found specific transcriptional regulators and differentially expressed genes between malignant and non-malignant groups. We identified more particularly abundant specifical intercellular communication in the malignant sample group and that may significantly influence the progression and spread of cancerous cells. Overall, our study provides the first single-cell atlas that comprehensively explains TSCC development and chemotherapy effects, thereby laying a new molecular foundation for therapeutic research in TSCC.